Will the Inducing and Maintaining Remission of Non-biological Agents and Biological Agents Differ for Crohn's Disease? The Evidence From the Network Meta-Analysis - Rui, Mingjun; Fei, Zhengyang; Wang, Yingcheng; Shi, Fenghao; Meng, Rui; Shang, Ye; Ma, Aixia; Li, Hongchao (Frontiers in Medicine, 2021)
Abstract: Background: Several drugs currently are available for the treatment of Crohn’s disease, including non-biological agents such as anti-inflammatory agents, steroids, immunosuppressive agents, and biologic agents such as anti-tumor necrosis factor (TNF), anti-α4β7 integrin, anti-alpha-4 integrin and anti-interleukin 12/23. However, the choice of treatments for induction and maintenance is still a challenge. The relevant comparison between non-biologic agents and biologic agents is few. In our research, we aimed to help making decisions, as well as providing clinicians and patients with medication references. Methods: We searched MEDLINE, Embase, and the Cochrane Central Register of controlled trials for relevant randomized controlled trials published through to July 2020 and systematic reviews published from January 2011 to December 2020. Search results were screened by 2 independent reviewers first by title and abstract and then by full text. Disagreements were resolved through discussion with a third reviewer. Results：54 randomized controlled trials were included in our analysis. For induction of remission, azathioprine (OR,3.5;95% Crl,1.4-8.9), infliximab (OR,4.1; 95% Crl,1.2-16.0), infliximab + azathioprine (OR,7.0; 95% Crl,1.2-41.0) and infliximab+ methotrexate (OR,7.8; 95% Crl,1.2-65.0) were more effective in first-line therapy than placebo. Adalimumab showed superiority to placebo in second-line therapy, but the range of SD was wide. For maintenance of remission, adalimumab (OR,2.24;95% Crl,1.17-4.76) and azathioprine (OR,2.05; 95% Crl,1.14-3.96) were more effective than placebo. Adalimumab (OR,0.56; 95%Crl,0.27-1.2), budesonide (OR,0.63; 95%Crl,0.26-1.6) and natalizumab (OR,0.65; 95%Crl,0.30-1.4) was associated with less risk of withdrawals when compared with placebo. Conclusion：For induction of remission, azathioprine, infliximab, and infliximab + azathioprine were more effective in first-line therapy. In second-line therapy, adalimumab was more effective but should be interpreted carefully. For maintenance of remission, adalimumab and azathioprine were more effective. Besides, adalimumab, budesonide, natalizumab had lower withdrawals. Therefore, biological agents were not always better than non-biological agents and they have their own advantages in different treatment methods of Crohn's disease.